Effect of workplace spirituality and servant leadership on service quality in higher education: A mediation model of job satisfaction - Desak Gede Chandra Widayanthi; I Made Yudana; Anak Agung Gede Agung; I Putu Wisna Ariawan (Global Business & Finance Review (GBFR), 2024)
Purpose: This study aimed to assess the impact of workplace spirituality and servant leadership on service quality in higher education. Design/methodology/approach: This was done by examining the function of job satisfaction as a mediator in this relationship. The study was carried out in a tertiary educational institution in Bali, Indonesia, and the data was analysed using PLS-based SEM (Structural Equation Model). Findings: The study findings indicate that (1) workplace spirituality and servant leadership in higher education have an impact on job satisfaction, (2) workplace spirituality and servant leadership do not have a direct effect on service quality in higher education, and (3) job satisfaction acts as a mediator between workplace spirituality, servant leadership, and service quality in higher education. Research limitations/implications: Research was carried out using scientific procedures and methods, but in its implementation, some limitations provide room for improvement in the future. Other variables that are decisive to service quality in education should be involved in future studies. Originality/value: Based on the findings, this study introduces a novel paradigm offering theoretical and practical advancements in ensuring quality of service in higher education. Additionally, it suggests fostering spirituality in the workplace and adopting servant leadership to guarantee lecturers' contentment to enhance the quality of service in higher education.
Keywords: 650; Workplace spirituality; Servant leadership; Service quality